1984
DOI: 10.1007/bf01972362
|View full text |Cite
|
Sign up to set email alerts
|

Immunologically induced pleural and peritoneal mast cell histamine release: Difference in responsiveness in relation to secretagogue and rat strain used

Abstract: Responsiveness was compared for cell populations harvested from the peritoneal and pleural cavities of rats with respect to histamine release induced by specific antigen, anti-IgE, and Con A. Cell populations were obtained from Fischer, PVG or Sprague-Dawley (SD) rats, which were either untreated or immunized with 10 micrograms ovalbumin together with 100 mg alum intraperitoneally. Mast cell histamine release was examined with crude cell populations. The results show that differences in response capacity to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, it has been reported that the cellstored histamine in the pleural cavity was potently reduced to 1/7 when actively sensitised rats were intrapleurally challenged by antigen [17], considerably different from the weak releasability of rat isolated pleural mast cells [18]. Thus, the weak histamine and serotonin release from the skin fragments induced by antigen challenge in the present experiments, compared to the PCA site, appeared to manifest the circumstantial difference between in vitro and in vivo experiments including antigen penetrating ability to the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that the cellstored histamine in the pleural cavity was potently reduced to 1/7 when actively sensitised rats were intrapleurally challenged by antigen [17], considerably different from the weak releasability of rat isolated pleural mast cells [18]. Thus, the weak histamine and serotonin release from the skin fragments induced by antigen challenge in the present experiments, compared to the PCA site, appeared to manifest the circumstantial difference between in vitro and in vivo experiments including antigen penetrating ability to the tissue.…”
Section: Discussionmentioning
confidence: 99%